(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2021)
Muhammad Syahrur’s point of view about hadith and sunnah was very different from hadith preacher expert. Syahrur declared that hadith was Prophet Muhammad’s life as a prophet (messenger) and hadith was the result of his interaction with the certain events in the different situation when he was alive. Muhammad Syahrur positioned hadith and sunnah as the result of history product which happened in Prophet Muhammad’s life and did not accommodate law legitimation. Further, he mentioned some rejected hadith practices, although it was identified as hadith shahih, or written in Shahihain. In understanding hadith, Syahrur equalized hermeneutics to ta’wil. He also referred to linguistic method proposed by Abu ‘Ali al-Farisi, which was presented by Ibn Jinni and Abd al-Qahir al-Jurjani, then inserted linguistic hermeneutics elements. Linguistic hermeneutics is the affirmation that every human language does not have synonym element. Then, every word might be disappeared throughout the history development, until create new utterance with the new meaning. Pandangan Muhammad Syahrur tentang hadis dan sunnah sangat berbeda dengan ulama hadis. Syahrur menyatakan bahwa hadis adalah kehidupan Nabi Muhammad Saw. sebagai seorang nabi (pembawa berita) dan hadis merupakan hasil interaksi beliau dengan kejadian-kejadian tertentu dalam situasi tertentu pula ketika beliau masih hidup. Muhammad Syahrur memosisikan hadis atau sunnah sebagai hasil dari produk sejarah yang terjadi dalam kehidupan Nabi Saw. dan tidak memuat legitimasi hukum. Bahkan ia memaparkan beberapa bentuk hadis yang ditolak meskipun hadis tersebut dikenal sahih, atau tertera di dalam kitab Shahihain. Dalam memahami hadis, Syahrur menyamakan hermeneutik dengan ta’wil dan ta’wil adalah hermeneutik. Ia juga berpegang kepada metode lingusitik Abu ‘Ali al-Farisi, yang direpresentasikan oleh Ibn Jinni dan ‘Abd al-Qahir al-Jurjani kemudian menambahnya dengan unsur-unsur hermeneutika lingustik. Hermeneutika linguistik adalah penegasan bahwa setiap bahasa manusia tidak memiliki unsur sinonimitas. Kemudian, setiap kata bisa saja lenyap sesuai dengan perkembangan sejarah, hingga mendatangkan ungkapan baru yang bermakna baru.